2015
DOI: 10.1111/inm.12116
|View full text |Cite
|
Sign up to set email alerts
|

To do good might hurt bad: Exploring nurses' understanding and approach to suffering in forensic psychiatric settings

Abstract: Patients in forensic psychiatric settings are likely to suffer not only from their mental illness but also from memories of criminal activities and, furthermore, from being involuntarily hospitalized. The aim of this study was to explore how nurses in forensic psychiatric care understand and approach patients' suffering. Data was generated by semi-structured interviews with psychiatric nurses from two different forensic psychiatric care units in Ascribing meaning to suffering, and 4) Being present in suffering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 31 publications
4
40
0
Order By: Relevance
“…According to Løgstrup (1983), interpretation is in the movement between perception and understanding. Our findings clearly indicate that nurses' perception were affected, which was also seen in other studies (Vincze et al, 2015). According to Løgstrup (1978), understanding can also create a distance and is linked to our preconceptions, where cultures and knowledge are embedded.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…According to Løgstrup (1983), interpretation is in the movement between perception and understanding. Our findings clearly indicate that nurses' perception were affected, which was also seen in other studies (Vincze et al, 2015). According to Løgstrup (1978), understanding can also create a distance and is linked to our preconceptions, where cultures and knowledge are embedded.…”
Section: Discussionsupporting
confidence: 83%
“…This indicates that the caring encounter is formed by patients' needs. The nurses described that facing patients' suffering sometimes required that the nurse take a step back-not to abandon, but rather to come closer, which is also described by Vincze, Fredriksson, and Wiklund Gustin (2015).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, nurses might distance themselves from patients to cope with such challenges (Jacob, Holmes & Buus, ; Vincze et al . ). Furthermore, Salzmann‐Erikson et al .…”
Section: Discussionmentioning
confidence: 97%
“…Vincze et al . () conducted a study to explore nurse–patient interactions within FMHN to understand and approach patients’ suffering. Vincze and colleagues found that some FMH nurses asserted the relevance of nurses’ emotional presence to ease the patients’ suffering as well as their genuine interest in the patients’ life worlds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation